Foreign direct investment, economic freedom and democracy - Kazemi, Morteza; Wan Ngah, Wan Azman Saini (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
This study examines the simultaneous role played by economic freedom and democracy in attracting foreign direct investment (FDI) inflows. In order to investigate this relation, data from a sample of 87countries over the period of 1981-2010 is employed. The main finding shows that the influence of economic freedom on FDI inflows is positive and significant. However, the results suggest that the democracy has no significant role in attracting FDI. The findings indicate that there is no evidence to support the idea that simultaneous occurrence of economic freedom and democracy are required to attract MNEs presence. Instead, the results reveal that improvement in economic freedom alone is sufficient to attract more FDI inflows. This finding is not consistent with Friedman’s view that free markets and political freedom are inseparable. Obviously, MNEs respond only to improvement in freedom of economic activity but not the level of democracy.